Building information modeling in local construction industry - Dabo Baba, Hammad (2010)
Building Information Modeling (BIM) is a new emerging approach to design, construction, and facility management in which a digital representation of the building process is being created to facilitate the exchange and interoperability of information in digital format. Despite the advantages derived from this paradigm, local construction industry is reluctant to deploy the technology in its service delivery. The objectives of the study include identifying the level of BIM tools utilization, identifying the barriers and strategies for the implementation of Building information modeling (BIM) in the local construction industry. Structured questionnaires were administered to 100 key players in the field of Architecture and Engineering randomly selected from within Kuala Lumpur region. Twenty Nine (29) respondents have appropriately answered and duly retuned the questionnaire. Data collected was analyzed using Analysis of Variance (ANOVA) and the hypotheses ware tested using t-test at 0.5% level of confidence. The study found that, BIM is been accepted by a substantial number of construction professional (Architects and Engineers). However, majority are still using AutoCAD in their design services. Moreover there is high correlation in terms of BIM Usage among Architects and Engineers but there is no correlation in the means responses of Architects and Engineers on the barriers to BIM implementation. In conclusion, the study has identified several strategies for Building Information modeling to be implemented and utilized in construction service delivery.